Economic analysis of a zero-carbon liquefied hydrogen tanker ship - Alkhaledi, Abdullah N. F. N. R.; Sampath, Suresh; Pilidis, Pericles (Elsevier, 2022)
The green hydrogen economy is considered one of the sustainable solutions to mitigate climate change. This study provides an economic analysis of a novel liquified hydrogen (LH2) tanker fuelled by hydrogen with a total capacity of ∼280,000 m3 of liquified hydrogen named ‘JAMILA’. An established economic method was applied to investigate the economic feasibility of the JAMILA ship as a contribution to the future zero-emission target. The systematic economic evaluation determined the net present value of the LH2 tanker, internal rate of return, payback period, and economic value added to support and encourage shipyards and the industrial sector in general. The results indicate that the implementation of the LH2 tanker ship can cover the capital cost of the ship within no more than 2.5 years, which represents 8.3% of the assumed 30-year operational life cycle of the project in the best maritime shipping prices conditions and 6 years in the worst-case shipping marine economic conditions. Therefore, the assessment of the economic results shows that the LH2 tankers may be a worthwhile contribution to the green hydrogen economy.
Keywords: Liquefied hydrogen; LH2 tanker; Hydrogen economy; Economic; Green economy; Tanker ship